2021
DOI: 10.1002/advs.202101940
|View full text |Cite
|
Sign up to set email alerts
|

Deeply Cyclable and Ultrahigh‐Rate Lithium Metal Anodes Enabled by Coaxial Nanochamber Heterojunction on Carbon Nanofibers

Abstract: Lithium metal anodes (LMAs) are the most promising candidates for high-energy-density batteries due to the high theoretical specific capacity and lowest potential. However, the practical application of LMAs is hampered by the short lifespan and unsatisfactory lithium utilization (<50%). An oxide-oxide heterojunction enhanced with nanochamber structure design is proposed to improve lithium utilization and cycling performance of LMA under ultrahigh rates. Typically, a MnO 2 -ZnO heterojunction provides high bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Obviously, our 10mg-Li@Pb@CC electrode demonstrates one of the best performance combinations in terms of overpotential and lifespan (See Table S3 † for the complete list of relevant literature data). 23,26,[41][42][43][44][45][46][47][48][49] To decipher the superiority of 10mg-Li@Pb@CC, we rst analyzed its composition and structure using XRD and XPS. As shown in ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, our 10mg-Li@Pb@CC electrode demonstrates one of the best performance combinations in terms of overpotential and lifespan (See Table S3 † for the complete list of relevant literature data). 23,26,[41][42][43][44][45][46][47][48][49] To decipher the superiority of 10mg-Li@Pb@CC, we rst analyzed its composition and structure using XRD and XPS. As shown in ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, our 10mg-Li@Pb@CC electrode demonstrates one of the best performance combinations in terms of overpotential and lifespan (See Table S3† for the complete list of relevant literature data). 23,26,41–49…”
Section: Resultsmentioning
confidence: 99%
“…Wen et al combined 1D Cu 3 P nanowires with Cu foil as a 3D Li host, working stably over 450 h at 2 mA cm −2 /2 mAh cm −2 [ 38 ]. Yang et al [ 33 ] reported that 2D MnZnO nanosheets/CNF infused with molten Li maintained 40 h at 50 mA cm −2 and 10 mAh cm −2 . Nevertheless, the modified Li anodes with high areal capacities (> 10 mAh cm −2 ) can only be performed (< 1000 h) at limited current densities (< 10 mA cm −2 ) [ 53 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by selective Li nucleation/growth through heterogeneous seeds presented by Cui's group [32], various lithiophilic materials (such as oxides [33][34][35], nitrides [36,37], and phosphides [38,39]) have been embedded into carbon frameworks to reduce the overpotential of Li nucleation and regulate uniform Li nucleation/growth. Besides, some lithiophilic compounds can react with molten Li to produce Li-based compounds (like, Li 3 N, Li 2 O, and Li 3 P) and metal, which facilitates the Li-ion transfer kinetics (e.g., Li + conductivity ≈ 10 −3 S cm −1 for Li 3 N), and electron conduction [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation